Soil erosion and land degradation due to hill clearance and urbanisation / Mohd Fozi Ali - Ali, Mohd Fozi (Universiti Teknologi MARA Cawangan Pahang, 2001)
Due to the population pressure a Iot of land is being cleared for cultivation settlement and lately by the process of urbanization The population of the humid tropic is expected to make up almost 33% of the total world population of about 6.5 billion by the year 2000. Most of the developing countries lie in the tropics and the urbanization process in still in its infancy where more development is expected to happen, The pressure for more development while land is searee has further deteriorated the environment as whole and land degradation in particular. This paper reviews the consequential impact of people's activities especially involving land clearing and urbanization that exacerbated the increase in erosion and thus land degradation in the tropics with mostly Malaysian examples.